Hydrothermal process reduced Pseudomonas aeruginosa PAO1-driven bioleaching of heavy metals in a novel aerated concrete synthesized using municipal solid waste incineration bottom ash - Biswal, Basanta Kumar (2021)
Development of innovative and sustainable technologies for recycling of municipal solid waste incineration bottom ash (IBA) are urgently needed for countries with limited land resources to prolong the lifespan of landfill sites. This study first attempted to reutilize IBA for synthesis of a novel aerated concrete by hydrothermal reaction. Moreover, impact of hydrothermal process on heavy metal bioleaching behavior of the synthesized material was investigated. Concrete specimens were prepared by optimum reuse of 20% IBA with replacement of cement in the mix matrix, then treated hydrothermally. A series of well-designed bioleaching experiments were carried out on samples of raw IBA, untreated and hydrothermally treated concretes in synthetic groundwater media using an environmental bacterium, Pseudomonas aeruginosa PAO1. The findings demonstrated that interactions between bacteria (strain PAO1) and IBA/concretes accelerated heavy metal leaching. Nonetheless, hydrothermal treatment has dramatic effects on immobilization of heavy metals because significant reduction (29–100%) of toxic metal (Cu, As, Pb and Cr) bioleaching observed. FE-SEM depicted a clear morphology change with plate, fibrous and needle-like structures, whereas XRD pattern indicated possible formation of a new calcium silicate hydrate (C-S-H) containing mineral (tobermorite) by hydrothermal reaction, and tobermorite might cause fixing of heavy metals by structural exchange of Ca2+ by metal ions. This study suggests production of construction materials using IBA by hydrothermal process could be an attractive option for recycling of IBA or similar properties of wastes.